Telepharmacy Model for Administering Opioids at Home to Palliative Care Patients in the New Normal Era, Yang Sisurat District, Maha Sarakham Province - แพงคำไหล ศุภชัย; วัชรวงษ์ไพบูลย์ พีร์; ปินะโต คำตัน (Journal of Health Science of Thailand, 2025)
This research aimed to develop and study the effects of a telepharmacy model for home opioid administration for palliative care patients in the new normal era. The research utilized a research and development approach under the seamless care concept, conducted in two cycles between January 2020 and March 2021. The sample consisted of 56 terminal cancer patients, 35 co-developers, and 20 trial participants. The developed model consisted of 11 main components: personnel training, CPG medication manual, medication administration, QR code innovation, VTR heart-healing medication clips, syringe driver medication mixing clips, “Relief Box” medication control, 1st and 3rd week follow-up and evaluation, real-time consultation system via Line Application, fast-track consult remote counseling and remote dispensing channels, monthly lesson debriefing, and the “Punboon Team” network. The research results found that adherence to CPGs increased from 65.00 percent to 80.50 percent, DRP corrections increased from 64.29 percent to 89.29 percent, and adherence to the 6R principles increased from 67.86 percent to 92.86 percent. The average pain score decreased from 7.2 to 3.1 points, patient satisfaction increased from 2.50 to 3.65, and staff satisfaction increased from 2.35 to 3.70 points. Thus, thistelepharmacy model is effective in administering opioids at home, reducing pain, increasing safety, and improving patient satisfaction, making it suitable for patient care in the new normal era.